Tayler Rule for a Highly Dollarized Country the Case for Albania - Zefi, Altin (European Journal of Multidisciplinary Studies, 2020)
Targeting nominal interest rate as a policy rule to achieve the primary purpose of stable prices has become a standard monetary policy for Central Banks. Albania switched in 2008 from targeting money supply, M3, to targeting nominal interest rate. Taylor Rule, as defined by John Taylor in his 1992 paper, has become widely used as a means to establish the policy interest rate for Central Banks. This paper implies a conceptual framework where policy rules are a means to a more effective monetary policy. The Taylor Rule has influenced the decision of policymakers on interest rate. Taylor presented his findings at the Carnegie-Rochester Conference on Public Policy in November 1992 and can be stated as a mathematical identity: r = p + .5y + .5(p - 2) +2. But can we use this rule universally? What about countries that are dollarized where the interest rate of loans paid in foreign currency depends on the interest rate of other countries? We expect to find that the standard Taylor Rule is not adequate and the domestic country, that is highly dollarized, should adopt an improved version that incorporates the expected interest rate, expected inflation and growth of the foreign country (ies) whose currency is present at large in the domestic economy.We propose a coefficient that puts downward pressure on the domestic nominal interest rate target when the foreign country’s (the country that has “dollarized” the domestic economy) lowers its nominal interest rate target. And when the nominal interest rate differential between tn and tn-1 -0 than this coefficient will have a upwards pressure.Thus we propose an adjusted Taylor Rule for foreign country interest rate and exchange rate to take the following form:iht = ?q i*t + ??Et?ht+1 + ?yyht + ?stqt + uhmt